Poor people's beliefs and the dynamics of clientelism. (July 2021) - Pellicer, Miquel; Wegner, Eva; Benstead, Lindsay J.; Lust, Ellen
Why do some poor people engage in clientelism whereas others do not? Why does clientelism sometimes take traditional forms and sometimes more instrumental forms? We propose a formal model of clientelism that addresses these questions focusing primarily on the citizen's perspective. Citizens choose between supporting broad-based redistribution or engaging in clientelism. Introducing insights from social psychology, we study the interactions between citizen beliefs and values, and their political choices. Clientelism, political inefficacy, and inequality legitimation beliefs reinforce each other leading to multiple equilibria. One of these resembles traditional clientelism, with disempowered clients that legitimize social inequalities. Community connectivity breaks this reinforcement mechanism and leads to another equilibrium where clientelism takes a modern, instrumental, form. The model delivers insights on the role of citizen beliefs for their bargaining power as well as for the persistence and transformation of clientelism. We illustrate the key mechanisms with ethnographic literature on the topic.